Decentralism versus centralism in Ottoman Anatolia, 1919-1922 - Gümüş, Fatih. (Thesis (M.A.) - Bogazici University. Atatürk Institute of Modern Turkish History, 2002., 2002)
The last few years of the Ottoman Empire saw the rise of a de-centralist/localist movement and approach in the country. The movement included some features which were very different from those of the traditional political approach of the Empire. It sought the foundation of an anti-bureaucratic and de-centralist administration in the country and demanded the establishment of local councils in local units such as the provinces (vilayets) and districts (nahiyes). This movement created tensions not only with the traditional power center in İstanbul, but also with the movement of a new political centralization, called here the Mustafa Kemal-led Political (National) Movement. The Mustafa Kemal-led Political Movement tried to establish a new political center in Anatolia, and in this process came into conflict with the local organizations or units. The Grand National Assembly was an arena in which these two diverse approaches came together, and within which the de-centralist/localist approach could openly show itself. The de-centralist/localist approach had the potential to radically reform the political structure of the Empire. To this aim, it offered some foundational laws. However, these offers were partly and unwillingly supported by the power group. In the end the supporters, of the de-centralist/localist approach were taken out of the GNA and the laws, or the articles of laws, and the drafts for laws which represented the de-centralist/localist approach were eradicated by the power group.
Keywords: Parliamentary practice -- Turkey.; Bureaucracy -- Turkey.